Reduction of daily life ischaemia by aspirin in patients with angina: underlying link between thromboxane A2 and macrophage colony stimulating factor. Issue 4 (12th March 2004) - Ikonomidis, I; Andreotti, F; Nihoyannopoulos, P
Abstract : Objectives: To evaluate whether aspirin reduces the incidence and frequency of daily life myocardial ischaemia in a cohort of patients with chronic stable coronary artery disease. Setting: Tertiary referral centre. Methods: 60 patients with chronic stable coronary artery disease underwent 48 hour Holter monitoring to assess the incidence and frequency of daily life myocardial ischaemia. Those with myocardial ischaemia (40/60) entered a double blind, crossover trial of aspirin (300 mg/day for three weeks) versus placebo. After each treatment arm, 48 hour Holter monitoring was repeated and urinary thromboxane (Tx) B2, 11-dehydro-TxB2, plasma prothrombin fragment F1+2, macrophage colony stimulating factor (MCSF), and interleukin (IL)-6 were measured. Results: Aspirin reduced the total number and duration of ischaemic episodes from 339 to 251 and from 1765 to 1365 minutes, respectively (p < 0.01 for both). TxB2 was also reduced from 0.2 to 0.1 ng/mg creatinine, 11-dehydro-TxB2 from 3.3 to 1.3 ng/mg creatinine, F1+2 from 1.5 to 1.2 nmol/l, MCSF from 991 to 843 pg/ml, and IL-6 from 3.5 to 2.9 pg/ml (p < 0.05 for all). 11-Dehydro-TxB2 excretion with and without aspirin was related to MCSF concentrations (p < 0.01), and the percentage reduction of MCSF by aspirin was related to the reduction of 11-dehydro-TxB2 (p < 0.05) and the reduction of the ischaemic burden compared with placebo (p < 0.05). Conclusions: In patients with daily life ischaemia, aspirin reduces the incidence and frequency of ischaemic episodes as well as the systemic concentrations of haemostatic/inflammatory markers. Aspirin may prevent transient coronary flow reductions through platelet, thrombin, and cytokine inhibition.